Value Premium and Country Risk as Dimensions to Estimate Conditional Returns: a Study of the Brazilian Market - Lilian de Castro Medeiros (FUCAPE Business School, 2015)
Asset pricing is a widely explored theme in the financial literature. Nevertheless, the phenomenon of value premium is still controversial, since although easily detected in developed and emerging markets, little is know about the economic forces that explain its existence. In this context, this article examines value premium in the Brazilian market and investigates the influence of the country risk variable as an additional risk factor for estimating conditional returns in this market not captured by value premium. For that, we employ a five-factor model, formulated by adding the country risk factor to the model of Carhart (1997). We apply the statistical procedure adopted by Fama & French (1993) to the period between 1994 and 2012, with data on nonfinancial companies listed on the BM&FBovespa. The results confirm the existence of value premium in the Brazilian market, and country risk and value premium together are significant factors to explain conditional returns.